Penerapan Metode Reading Corner untuk Meningkatkan Minat Baca dan Pemahaman Teks Non Fiksi: Penelitian - Ryzna Dewi Anitania Wibowo; Sri Nurhayati; Husni Mubarok (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Applying reading corner at SD IT Al-Ikhlas Tlogowungu helps to raise student reading interest and understanding especially for nonfiction texts. Background reveals the low level of reading interest in Indonesia, where just one in five people reads regularly. Survey results revealed that many people still cannot read and write despite high literacy rates. Low reading interest hurts students' capacity to read nonfictional texts requiring structural analysis and understanding. The approach employed in this study is qualitative descriptive; data gathering methods include observation, interview, and documentation. Observasi is used to find out the state of the classroom; interviews with the head teacher, teachers, and students; and written relevant data is gathered through documentation. With the goal of improving students' book access and encouraging them to read more, the reading corner idea offers cozy and interesting space for reading inside the classroom. Studies show that the use of reading corner successfully raised students' understanding of nonfictional texts and their enthusiasm in reading. Students grow more active and enjoy reading, therefore their reading frequency also rises. This approach also helps students become more aware of the advantages of reading, therefore developing their capacity to interpret nonfictional texts.